2021
DOI: 10.3389/fonc.2020.616717
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs in the Metastasis of Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is a common malignant tumor worldwide. Metastasis is the main cause of the death of OSCC patients. Long noncoding RNAs (lncRNAs), one of the key factors affecting OSCC metastasis, are a subtype of RNA with a length of more than 200 nucleotides that has little or no coding potential. In recent years, the important role played by lncRNAs in biological processes, such as chromatin modification, transcription regulation, RNA stability regulation, and mRNA translation, has been g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 134 publications
(158 reference statements)
0
12
0
Order By: Relevance
“…Evidence also showed that different functional studies revealed the role of lncRNAs in oncogenesis, tumor-suppression, and chemoresistance as well as governing virtually every physiological cell process ( Figure 1 ). Abnormal lncRNAs are involved in many aspects of cancer cell processes including cell proliferation, apoptosis, invasion and metastasis [ 16 ], epithelial–mesenchymal transition (EMT), and drug resistance [ 17 ]. Moreover, lncRNAs even affect the outcome of patients such as lymph node metastasis, distal metastasis, and postoperative recurrence [ 18 ].…”
Section: Roles Of Lncrna In Osccmentioning
confidence: 99%
“…Evidence also showed that different functional studies revealed the role of lncRNAs in oncogenesis, tumor-suppression, and chemoresistance as well as governing virtually every physiological cell process ( Figure 1 ). Abnormal lncRNAs are involved in many aspects of cancer cell processes including cell proliferation, apoptosis, invasion and metastasis [ 16 ], epithelial–mesenchymal transition (EMT), and drug resistance [ 17 ]. Moreover, lncRNAs even affect the outcome of patients such as lymph node metastasis, distal metastasis, and postoperative recurrence [ 18 ].…”
Section: Roles Of Lncrna In Osccmentioning
confidence: 99%
“…Oral cancer, which is associated with tissues in the mouth and throat, is a subtype of a larger group of cancers known as head and neck cancer. Although there are various forms of oral cancer, approximately 90% of the oral cancers are classified as squamous cell carcinomas because the mouth and throat are lined almost entirely with squamous cells (2,3) . Gingivobuccal complex cancer is a type of oral squamous cell cancer and has been reported to be the most common form of oral cancer in India among men and is quite predominant in countries where tobacco use is rampant.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need to properly identify and validate the expression of lncRNA in the gingivobuccal complex. Despite the presence of glaring evidence for lncRNA playing a critical role in the biological processes of human diseases, very few efforts have been made to identify their association with gingivobuccal cancer and assess their prognostic (2,5) . Furthermore the interest in the identification of lncRNA signatures in Gingivobuccal Squamous Cell Carcinoma (GBSCC) stems from the idea of identification of non-invasive biomarkers present in the saliva for early detection of oral cancer (6,7) .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, the advent of high-throughput sequencing techniques has enabled identification of a continuously rising amount of dysregulated lncRNAs associated with oral cancer [ 17 , 18 ]. Among these transcripts, only a few have been thoroughly investigated for their mechanisms of action, whereas the functional details of most remain largely uncharacterized [ 19 , 20 , 21 , 22 ]. Within the long-standing intense debate about the functionality of most, if not all, of these lncRNAs, a precursor–product relationship between junk RNA and functional lncRNAs has recently been suggested, in which junk transcripts may provide the raw material for the evolution of diverse lncRNAs, through a non-adaptive mechanism [ 23 ].…”
Section: Introductionmentioning
confidence: 99%